If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = 7x + 64 Reorder the terms: -13 = 64 + 7x Solving -13 = 64 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -13 + -7x = 64 + 7x + -7x Combine like terms: 7x + -7x = 0 -13 + -7x = 64 + 0 -13 + -7x = 64 Add '13' to each side of the equation. -13 + 13 + -7x = 64 + 13 Combine like terms: -13 + 13 = 0 0 + -7x = 64 + 13 -7x = 64 + 13 Combine like terms: 64 + 13 = 77 -7x = 77 Divide each side by '-7'. x = -11 Simplifying x = -11
| 37+12x=85 | | -4-8x=36 | | 8x-8=7x+14 | | -44=-3x-2 | | 2x+17=53 | | 8x-8=7x+4 | | -12=x-21 | | 4x-7=9x | | -57=-12+3x | | 29=-8x-3 | | 3-x=-4 | | 11-3v-u= | | 0.6x-0.8(3-x)=2.5 | | -3x=-10+2x | | y^2-18x=0 | | 9x=16+5x | | 6x-3=27x | | -6u-27=7(u-2) | | =-3[x+2]2+5 | | 5x+6=4x+5 | | 5(z-2)+4z-4= | | 4ln(x-7)=8 | | 5k-8=1(9) | | 2u-6=-2 | | Y^2+3y-6=0 | | 70=3w+16 | | 4(z-2)+8z-1= | | c=2.88(6)+14.18 | | 2(5z-1)-3(z-2)= | | x+7-15+(-4)=24 | | 5x/2-5x-10/10=0 | | 0.875h-0.625=2 |